Լազարյանները և ռուսահայ գաղթավայրերը - Օհանյան, Հրանտ
The article discusses the relationship and cooperation between the Lazarians and the Armenian communities in Russia in the first half of the 19th century, whose main goal was preserving the privileges of the Armenian communities in Russia. The Lazarians’ archive in Matenadaran contains numerous documents concerning their many-sided support of the Armenian communities in Russia. The prominent representatives of the family, Hovakim (Yekim) Lazarian (1743-1826) and his sons and successors Khachatur (Christopher) (1789-1871) and Hovhannes (Ivan) (1786-1858) Lazarians provided their immediate support and sponsorship for almost all issues concerning Russian-Armenians, properly presenting them to the Russian authorities. They were always engaged in pro-Armenian activities, maintaining close relations with local Armenian dioceses and communities. The author has studied more than two dozen archival documents that confirm the Lazarians’ active participation in the life of Armenian communities. В статье исследуются факты тесных связей и взаимодействий между Лазаревыми и армянскими колониями в первой половине XIX века, основной целью которых было сохранение привилегий армянских колоний. В фонде Лазаревых в Матенадаране хранится множество документов, касающихся всесторонней поддержки, оказываемой Лазаревыми армянским колониям. Выдающиеся представители рода – Еким (Оваким) Лазаревич (1743-1826) и продолжатели его дела, сыновья Иван (Оганнес) (1786-1858) и Христофор (Хачатур) (1789-1871) Лазаряны оказывали непосредственную поддержку и покровительство во всех вопросах, касающихся армянских колоний, должным образом представляя их российским властям, занимались проармянской деятельностью, поддерживали постоянный контакт с местными армянскими епархиями и общинами. Исследование основано на изучении более двух десятков архивных документов, которые подтверждают активное участие Лазаревых в жизни армянских общин.
Keywords: Պատմություն; Ռուսահայ գաղթավայրեր